Human Recombinant Antithrombin (ATryn®) Administration Improves Survival and Prevents Intravascular Coagulation after Intraportal Islet Transplantation in a Piglet Model. Issue 2 (February 2017) - Gmyr, Valery; Bonner, Caroline; Moerman, Ericka; Tournoys, Antoine; Delalleau, Nathalie; Quenon, Audrey; Thevenet, Julien; Chetboun, Mikael; Kerr-Conte, Julie; Pattou, François; Hubert, Thomas; Jourdain, Merce
Human islet transplantation is a viable treatment option for type 1 diabetes mellitus (T1DM). However, pancreatic islet inflammation after transplantation induced by innate immune responses is likely to hinder graft function. This is mediated by incompatibility between islets and the blood interface, known as instant blood-mediated inflammatory reaction (IBMIR). Herein we hypothesized that portal venous administration of islet cells with human recombinant antithrombin (ATryn ® ), a serine protease inhibitor (serpin), which plays a central role in the physiological regulation of coagulation and exerts indirect anti-inflammatory activities, may offset coagulation abnormalities such as disseminated intravascular coagulation (DIC) and IBMIR. The current prospective, randomized experiment was conducted using an established preclinical pig model. Three groups were constituted for digested pancreatic tissue transplantation (0.15 ml/kg): control, NaCl 0.9% ( n = 7); gold standard, heparin (25 UI/kg) ( n = 7); and human recombinant ATryn® (500 UI/kg) ( n = 7). Blood samples were collected over time (T0 to 24 h), and biochemical, coagulation, and inflammatory parameters were evaluated. In both the control and heparin groups, one animal died after a portal thrombosis, while no deaths occurred in the ATryn®-treated group. As expected, islet transplantation was associated with an increase in plasma IL-6 or TNF-α levels in all three groups. However, DIC was only observed in the control group, an effect that was suppressed after ATryn® administration. ATryn® administration increased antithrombin activity by 800%, which remained at 200% for the remaining period of the study, without any hemorrhagic complications. These studies suggest that coadministration of ATryn® and pancreatic islets via intraportal transplantation may be a valuable therapeutic approach for DIC without risk for islets and subjects.